The correlation between the morphosyntactic marking of nominal predicates and the aspect of the verb - Vaičiulytė-Semėnienė, Loreta (Lietuvių kalba, 2012)
On the basis of the foreign linguistic tradition, in the present article distinction is made between the lexical and the grammatical aspect. The article deals with the possible connection between marking noun predicates with inherent features of auxiliary and the grammatical aspect. It is considered that with respect to the dynamics aspect, morphosyntactic marking is gradual. There is a tendency to additionally mark perfectivity by using prefixes of perfective aspect verbs and/or by morphosyntactic means.
Keywords: none